Illocutionary Acts Used in the Dead Poets Society Movie - Robiah AL Adawiyah; Irma Diani; Azwandi Azwandi (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to describe the category of illocutionary and reaction to illocutionary interlocutors expressed by the speakers used in the Dead Poets Society movie. The method used in this study is a qualitative descriptive method. The object of the research is the Dead Poets Society movie script. Based on data analysis, the researcher found 72 utterances illocutionary acts, the dominant ones are Verdictives, namely Estimating and Behabitives, namely Complimenting, while the reaction of the interlocutor to illocutionary acts is dominated by Behabitives illocutionary acts, namely Applauding, and Expositives illocutionary acts, namely Denying. The researcher assumes the tendency of using inspired speech acts by the genre of movie, namely tragedy and drama because this movie features several characters show interest in poetry, and have conflicts between students, parents, and teachers when taught by Mr. Keating is considered to have deviated in principle from Welton Academy. The results of this study can be used as a reference in studying speech acts in pragmatics because, in this study, the researcher classified the types of illocutionary acts more easily based on Austin's theory.